The Role of Circadian Rhythms in Fatal Arrhythmias and the Potential Impact of Intervention for Sleep-Disordered Breathing - Aizawa, Yoshiyasu; Kohno, Takashi; Yuasa, Shinsuke; Fukuda, Keiichi (Current Pharmaceutical Design, 2015)
There exist circadian patterns in the occurrence of sudden cardiac death. The suprachiasmatic nuclei is the ‘master clock’ in mammalian bodies. Furthermore, several circadian genes have been successfully isolated in basic studies and a huge variety of key players form the human circadian rhythm. Obvious circadian patterns are present in the occurrence of critical events, but those characteristics differ greatly according to each disease. In this review we summarized the current understanding of the basic mechanism and association with specific cardiovascular diseases that demonstrate a circadian onset of fatal events. We also summarized the recent deep understanding of sleep-disordered breathing. The close relationship between sleep-disordered breathing and cardiovascular diseases may provide us with the possibility of a novel intervention against sudden cardiac death.
Keywords: sleep-disordered breathing